Education and Application of Deep Breathing Relaxation Techniques as a Means of Maintaining Psychological Health - Halima Aulia Ita Maghfiroh; Ahmad Daniel; Eka Budi Pranata; Theresa Gloria Estefania Beka; Yulia Ashafan (Jurnal Indonesia Sosial Sains, 2026)
Children living in orphanages are vulnerable to psychological distress due to limited emotional support, shared living environments, and previous adverse experiences. This community service program aimed to improve foster children’s knowledge and practical skills in stress management through education and deep breathing relaxation techniques at Griya Yatim and Dhuafa Solo Branch. The program employed a face-to-face educational approach consisting of a pre-test, counseling session, direct practice of the 4-2-6 deep breathing technique, discussion, and post-test evaluation. Of the 16 registered foster children, 14 participated in all stages of the activity. The results showed a substantial improvement in participants’ knowledge following the intervention. The proportion of participants in the good knowledge category increased from 21.4% in the pre-test to 85.7% in the post-test, while the poor knowledge category decreased from 28.6% to 0%. The mean knowledge score increased from 52.86 to 88.57. Participants were also able to perform the breathing technique correctly and reported feeling more relaxed after the exercise. In conclusion, education combined with direct deep breathing relaxation practice effectively improved foster children’s understanding of psychological health and stress management. This approach provides a simple, low-cost, and applicable strategy for supporting psychological well-being in orphanage settings. Regular implementation of this intervention may help strengthen independent coping skills and emotional self-regulation among foster children in a sustainable manner.